Pastel Tutup Daging Ayam dan Daun Kelor sebagai Pemberian Makanan Tambahan Balita Stunting di Puskesmas Dinoyo Kota Malang: Kajian Nilai Gizi, Mutu Protein dan Daya Terima - Fitria Kurniawati; I Nengah Tanu Komalyna (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Stunting is a growth problem caused by insufficient intake of nutrients for a long time. Casserole as supplementary feeding expected to be able handle stunting. Objective of this study was to examine the characteristics of the nutritional fact, protein quality and acceptance of casserole using Completely Randomized Design. There were 15 semi-trained panelists involved in the organoleptic tests. There were 5 stunted toddlers as the result of purposive sampling that tested to the acceptance of casserole as supplementary feeding. The research was conducted at the Dinoyo Puskesmas, Ketawanggede Village, Malang City, from 15 to 21 September 2020. The parameters were organoleptic test, best treatment, nutritional fact and acceptability. The data were analyzed with Microsoft Office Excel 2007. The treatments were P1 (95% chicken and 5% Moringa oleifera) and P2 (85% chicken and 15% Moringa oleifera). The results of the test organoleptic hedonic showed that P1 and P2 had a faded yellow color, the taste of P1 was savory and P2 was very tasty, the aromas of P1 and P2 were less pleasant and unpleasant, the textures of P1 and P2 were rather soft and tender. The hedonic organoleptic test results showed the color, taste, aroma and texture P1 and P2 in the average of panelists like. The conclusion the average acceptance of casserole as supplementary feeding is 65% due to the taste and texture that is less liked the toddlers.